Children left at home alone: the construction of a social problem - Calcraft, Rebecca (2004)
The question of when a child is old enough to be left at home alone, and under what circumstances, is a dilemma faced by many parents and professionals. Adopting a social constructionist perspective of social problems, this thesis explores professional perceptions and policy responses to the issue of children left at home alone since the passing of the Children Act in 1989. The law in England and Wales does not specify an age at which it is deemed safe to leave a child unsupervised at home, a practice sometimes referred to as 'self-care'. Professionals respond to the issue through non-legalistic, more persuasive interventions. The media also plays a role in regulating parenting practices, as demonstrated in the early 1990s, when the British press covered a number of stories involving parents who left their children at 'home alone'. The issue continues to bubble up from time to time, but calls for more specific law to manage the problem have gone unheeded.